THE BASIC FORM OF THE VERBAL ALLOMORPHS WITHIN MORPHONOLOGICAL CHANGES IN THE ALBANIAN LANGUAGE (Journal of Contemporary Philology, 2019)
The  paper  examines newspaper  headlines  written  in  Macedonian  with  the  aim  to determine their syntactic characteristics. The analysis of the collected examples shows thatthe  headlines  written  in  standard  Macedonian  have  identical  syntactic  features with  those  in  other  languages  already  identified  in  previous  research.  However,  the headlines analyzed in this paper also display certain specific  features attributable  to the  syntactic  constructions characteristic  of  Macedonian.The  findings  identified several  features,  such  as:  maximum  condensed  information  leading  to  syntactic ambiguity of the headlines, depending on whether the headlines are treated as a simple or compound sentence; reduction of the information into a single,complexsyntagma, which poses the dilemma of whether the activity coded by the predicate is completed or  not;  the  dual  interpretation  of  the  participial  adjective,  which  determines  the sentence  as  active  or  passive;  the  use  of asyndetic  structures  and  other  types  of subordination  strategies  in  complex  sentences,  which  strengthens  their  syntactic ambiguity and contributes to their over-informativeness.
Keywords: morphonology; morphonological changes; verbs; Gheg dialect